2012
DOI: 10.1158/1078-0432.ccr-12-0490
|View full text |Cite
|
Sign up to set email alerts
|

A Long-term Prospective Population Pharmacokinetic Study on Imatinib Plasma Concentrations in GIST Patients

Abstract: Purpose: Imatinib minimal (trough) plasma concentrations after one month of treatment have shown a significant association with clinical benefit in patients with gastrointestinal stromal tumors (GIST). Considering that a retrospective pharmacokinetic analysis has also suggested that imatinib clearance increases over time in patients with soft tissue sarcoma and GIST, the primary aim of this study was to assess systemic exposure to imatinib at multiple time points in a long-term prospective population pharmacok… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 21 publications
5
77
2
Order By: Relevance
“…We thank Chatelut and colleagues for their interest in our prospective population pharmacokinetic analysis of imatinib exposure in patients treated for gastrointestinal stromal tumor (1). In their letter to the editor, these authors suggested an alternative explanation for the approximately 30% decrease in imatinib exposure after a treatment duration of 3 months or longer.…”
mentioning
confidence: 99%
“…We thank Chatelut and colleagues for their interest in our prospective population pharmacokinetic analysis of imatinib exposure in patients treated for gastrointestinal stromal tumor (1). In their letter to the editor, these authors suggested an alternative explanation for the approximately 30% decrease in imatinib exposure after a treatment duration of 3 months or longer.…”
mentioning
confidence: 99%
“…The typical total carrying capacity (both lesions accounted for) was estimated to 1,730 and 1,818 mL for V actual and V ellipsoid , respectively; these values are similar to literature values of liver volume in living donors ( c.a . 1,500 mL)36 and to the baseline liver volume in a similar GIST patient population14 (median = 1,755; range = 1,112–3,354 mL), of which some of the patients reported in this study were part, and, therefore, clinically plausible. When tumor size is very small compared to the carrying capacity, logistic growth can be approximated by an exponential growth with rate constant K G .…”
Section: Discussionmentioning
confidence: 59%
“…Accordingly, the imatinib target trough concentration of 1100 ng/mL that has been proposed for GISTs 59 only applies to samples collected specifically on day 29. 157 No systematic change in imatinib trough concentrations has been observed in CML. 159 As such, TDM sampling for some molecules is indication specific.…”
Section: Temporal Changes In Pharmacokineticsmentioning
confidence: 99%